TRANSAKSI DERIVATIF DALAM PERSPEKTIF EKONOMI SYARIAH - Dimyati, - - (Irtifaq, 2015)
A product of Islamic financial that are still debating is the products derived from derivative transactions. It is carried out to support business investment. In Islam, money does not as a medium of exchange (medium of exchange) and is not a traded commodity. So it actually does not recognize the term sharia money trading. On the other hand, Islam allows the buying and selling of commodities either in cash or tough. In this case the company shares or bonds can be categorized as a commodity because it can not be considered as appropriate the money that serves as a medium of exchange for all goods. Keywords: Derivative Transactions, Salam, Istishna', Arbūn, Khiyar Shart